2014
DOI: 10.1002/pros.22869
|View full text |Cite
|
Sign up to set email alerts
|

Serum tri‐ and tetra‐antennary N‐glycan is a potential predictive biomarker for castration‐resistant prostate cancer

Abstract: These results suggest that the overexpression of tri- and tetra-antennary N-glycan may be associated with the castration-resistant status in PC and may be a potential predictive biomarker for CRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 28 publications
(37 reference statements)
2
64
1
Order By: Relevance
“…Several studies have shown that differences in serum N-glycan profiles between diseased and benign states analyzing high-throughput, comprehensive and quantitative N-glycomics may be useful in the diagnosis or prognosis of diseases [11][12][13][14]19]. A few studies have investigated the use of serum N-glycans as diagnostic markers for UC, including UTUC [13,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that differences in serum N-glycan profiles between diseased and benign states analyzing high-throughput, comprehensive and quantitative N-glycomics may be useful in the diagnosis or prognosis of diseases [11][12][13][14]19]. A few studies have investigated the use of serum N-glycans as diagnostic markers for UC, including UTUC [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…A 10-µL aliquot of the purified Igs fractions were analyzed using the glycoblotting method [11,12,15,33] on a Sweetblot instrument (System Instruments, Hachioji, Tokyo, Japan). Then, the resulting benzyloxiamine (BOA)-labelled glycans were detected by matrix-assisted laser desorption time-of-flight (MALDI-TOF) mass spectrometry (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) ( Figure A1a-f).…”
Section: Serum N-glycomics Of Igs Performed By Using the Glycoblottinmentioning
confidence: 99%
“…A 10-µL aliquot of whole serum or a Igs fraction purified from whole serum was processed by using the glycoblotting method [8][9][10][11][12][13][14]21] and a controlled automated SweetblotTM instrument (System Instruments, Hachioji, Japan). Then, the resulting BOA-labeled glycans were detected by MALDI-TOF MS (Ultraflex 3 TOF/TOF mass spectrometer; Bruker Daltonics, Bremen, Germany) (Figure 8).…”
Section: Glycoblotting Methods and Mass Spectrometrymentioning
confidence: 99%
“…N-glycan structures frequently change in cancer and are linked to disease progression and metastasis (Taniguchi & Kizuka 2015). Increased levels of branched and cryptic N-glycans are common in prostate cancer, have been linked to EMT and metastasis and are currently being investigated as potential diagnostic markers (Kyselova et al 2007, Newsom-Davis et al 2009, Pinho et al 2012, Wang et al 2013, Ishibashi et al 2014, Li et al 2014a, Taniguchi & Kizuka 2015. The expression of six enzymes with roles in N-glycan processing (EDEM3, ST6GAL1, B4GALT1, UGGT1, ALG2 and NEU1) is controlled by the AR in prostate cancer cells .…”
Section: N-glycan Biosynthesis (Ost Complex N-glycan Processing)mentioning
confidence: 99%